1990
DOI: 10.1093/bja/64.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia, Movement and Emesis

Abstract: One hundred and eighty-two women undergoing dilatation and curettage were allocated randomly to receive premedication comprising temazepam, papaveretum-hyoscine or placebo. The temazepam recipients reported significantly fewer episodes of postoperative nausea. Movement was blamed by 66% of patients who identified a cause for nausea. These patients had higher scores on a motion sickness susceptibility questionnaire and were more likely to have been treated previously for nausea or vomiting. It may be possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 5 publications
(2 reference statements)
3
16
0
4
Order By: Relevance
“…Kamath et al reported that 66% of their patients who could identify a cause for postoperative nausea blamed movement [11]. Muir et al ............................................................................................................................................................................................................................................. …”
Section: Discussionmentioning
confidence: 99%
“…Kamath et al reported that 66% of their patients who could identify a cause for postoperative nausea blamed movement [11]. Muir et al ............................................................................................................................................................................................................................................. …”
Section: Discussionmentioning
confidence: 99%
“…Sudden motion, changes in position, or even transport from the PACU to the ward can precipitate nausea and vomiting in patients who have received opioid compounds. Kamath et al also demonstrated that 66% of PONV was related to movement (20). …”
Section: Discussionmentioning
confidence: 99%
“…10 The higher incidence of PONV after discharge in both studies may be attributable to the continued effect of morphine stimulation of the vestibular apparatus with the increase in activity after discharge home. 11 The incidence of PONV varies in previous studies of perioperative morphine. In gynecological patients, 10 mg morphine im administered preoperatively resulted in a 9-15% incidence of nausea and a 3-45% incidence of vomiting.…”
Section: Discussionmentioning
confidence: 99%